Pressure and angle-dependent Shubnikov-de Haas studies of the spin-density-wave state of alpha-(BEDT-TTF)(2)KHg(SCN)(4) - Hayes, W; House, A; Lubczynski, W; Blundell, S; Singleton, J; Kurmoo, M; Day, P (1997)
Shubnikov-de Haas (SdH) experiments involving pressures of up to 15 kbar, temperatures as low as 500 mK and magnetic fields as high as 17 T have been carried out in order to probe the proposed phase transition of alpha-(BEDT-TTF)(2)KHg(SCN)(4) from a spin-density-wave (SDW) state at a pressure of P-c similar to 5 kbar. SdH measurements have also been carried out with the sample at a variety of field orientations. Frequencies of lambda approximate to 181 T, alpha approximate to 671 T, mu approximate to 775 T, nu approximate to 856 T and beta approximate to 4270 T are observed in the Fourier spectra of the ambient pressure oscillations. The lambda, mu, nu and beta oscillations and also the large second harmonic component of the alpha orbit SdH waveform are not observed in the high field (>23T) metallic state, implying that they are a characteristic of the ambient pressure SDW state. Pressure suppresses the lambda, mu and nu frequencies but the a and P orbits are seen at all pressures. The large second harmonic of the waveform of the a orbit SdH is initially suppressed by pressure but reemerges above similar to 10 kbar. The origins of this are discussed.